2016
DOI: 10.1155/2016/5329291
|View full text |Cite
|
Sign up to set email alerts
|

Fault Tolerant Controller Design for a Faulty UAV Using Fuzzy Modeling Approach

Abstract: We address a fault tolerant control (FTC) issue about an unmanned aerial vehicle (UAV) under possible simultaneous actuator saturation and faults occurrence. Firstly, the Takagi-Sugeno fuzzy models representing nonlinear flight control systems (FCS) for an UAV with unknown disturbances and actuator saturation are established. Then, a normal H-infinity tracking controller is presented using an online estimator, which is introduced to weaken the saturation effect. Based on the normal tracking controller, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The observer TS (20) asymptotically converges to (17) if there exist matrices P = P T > 0, M i , satisfying the following matrix inequality:…”
Section: Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…The observer TS (20) asymptotically converges to (17) if there exist matrices P = P T > 0, M i , satisfying the following matrix inequality:…”
Section: Theoremmentioning
confidence: 99%
“…In particular, it has been shown that a TS dynamic model obtained through the nonlinear sector transformation approach can describe the overall behavior of a highly complex nonlinear system with a high degree of accuracy [11,14]. As a result, its applicability in designing controllers, diagnosis systems, and observers, among others, has become of high importance; see, for instance, [15][16][17] and references therein. Applications on vehicles can be found in the literature; for example, in [4], a predictive control strategy using a TS model is presented to control the velocity in an EV, and the authors in [18] proposed a linear parameter varying (LPV) controller in order to control the tracking of the longitudinal velocity and the yaw velocity of the EV.…”
Section: Introductionmentioning
confidence: 99%